Factors determining the sensitivity to proteasome inhibitors of multiple myeloma cells - Pelon, Marta; Krzeminski, Patryk; Tracz-Gaszewska, Zuzanna; Misiewicz-Krzeminska, Irena (Frontiers in Pharmacology, 2024)
Multiple myeloma is an incurable cancer that originates from antibody-producing plasma cells. It is characterized by an intrinsic ability to produce large amounts of immunoglobulin-like proteins. The high rate of synthesis makes myeloma cells dependent on protein processing mechanisms related to the proteasome. This dependence made proteasome inhibitors such as bortezomib and carfilzomib one of the most important classes of drugs used in multiple myeloma treatment. Inhibition of the proteasome is associated with alteration of a number of important biological processes leading, in consequence, to inhibition of angiogenesis. The effect of drugs in this group and the degree of patient response to the treatment used is itself an extremely complex process that depends on many factors. At cellular level the change in sensitivity to proteasome inhibitors may be related to differences in the expression level of proteasome subunits, the degree of proteasome loading, metabolic adaptation, transcriptional or epigenetic factors. These are just some of the possibilities that may influence differences in response to proteasome inhibitors. This review describes the main cellular factors that determine the degree of response to proteasome inhibitor drugs, as well as information on the key role of the proteasome and the performance characteristics of the inhibitors that are the mainstay of multiple myeloma treatment.